2020
DOI: 10.3390/cancers12113408
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 14 Day Infusional Ifosfamide for Management of Soft-Tissue and Bone Sarcoma: A Single Centre Retrospective Cohort Analysis

Abstract: Ifosfamide is used to treat soft-tissue sarcoma (STS) and bone sarcoma (BS), with improved efficacy at doses above 9 g/m2/cycle. To mitigate treatment-associated toxicity with higher doses, continuous infusional ifosfamide is increasingly used. However, clinical outcome data remain limited. Single-centre retrospective analysis of patients treated with four-weekly infusional ifosfamide (14 g/m2/14d) between August 2012 and February 2019 was conducted. Radiological response, progression-free survival (PFS), over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Ifosfamide-induced encephalopathy, although rare, is a well-known adverse event which can occur in 2–5% of patients who have received the drug either intravenous or orally [ 36 , 37 ] It can occur 12 to 146 h after the start of the infusion with different clinical features (from mild to life-threatening symptoms) [ 36 , 37 ]. Notably, the cohort of patients analyzed in this study didn’t show any neurological toxicities, consistent with the previously reported association with continuous infusion and fewer side-effects, including low incidence of neurological events [ 19 22 ]. In fact, a prolonged infusion induces a reduction in the half-life of the active metabolites of ifosfamide, increasing their clearance and giving rise to a lower plasma peak, without changing the drug’s alkylating activity [ 19 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ifosfamide-induced encephalopathy, although rare, is a well-known adverse event which can occur in 2–5% of patients who have received the drug either intravenous or orally [ 36 , 37 ] It can occur 12 to 146 h after the start of the infusion with different clinical features (from mild to life-threatening symptoms) [ 36 , 37 ]. Notably, the cohort of patients analyzed in this study didn’t show any neurological toxicities, consistent with the previously reported association with continuous infusion and fewer side-effects, including low incidence of neurological events [ 19 22 ]. In fact, a prolonged infusion induces a reduction in the half-life of the active metabolites of ifosfamide, increasing their clearance and giving rise to a lower plasma peak, without changing the drug’s alkylating activity [ 19 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ifosfamide is an alkylating chemotherapy agent that has been widely used in R/R OS treatment [ 12 18 ], either alone or in combination with other agents (Table 1 ), demonstrating a role in improving both Disease Control Rate (DCR) and Progression Free Survival (PFS) [ 12 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of locally advanced or metastatic sarcoma, these aggressive regimens achieve response rates of only 12% for doxorubicin and 6% to 8% for ifosfamide as single agents (17). For ifosfamide treatment in osteosarcoma, one retrospective study yielded a single case of improvement among 13 patients (18). A second study reported an ORR of 20% after high-dose ifosfamide treatment in patients with relapsed osteosarcoma; the median DOR was 7 months, similar to that seen in the presented study (8 months; ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, gemcitabine, docetaxel, and dacarbazine show only weak activity against synovial sarcoma ( Table 10 ). Retrospective studies confirmed these conclusions ( Ferrari et al, 2015 ; Sanfilippo et al, 2015 ; Desar et al, 2018 ; Pender et al, 2018 ; Stacchiotti and Van Tine, 2018 ; Carter et al, 2020 ; Kogushi et al, 2020 ). A retrospective study demonstrated that trabectedin had activity in synovial sarcoma ( Sanfilippo et al, 2015 ).…”
Section: Efficacy Of Different Drugs In Different Sts Histological Su...mentioning
confidence: 57%
“…Therefore, doxorubicin is still considered the first choice of chemotherapy for advanced STSs ( Lorigan et al, 2007 ). However, ifosfamide may be superior to doxorubicin in synovial sarcoma ( Nielsen et al, 2000b ; Carter et al, 2020 ).…”
Section: Efficacy Of Different Drugs In Stssmentioning
confidence: 99%